Analysis of Factors Influencing the Progressivity of Refraction Status on the Employees of Widya Husada University - Cahyaningsih, Oktaviani; Rochmayani, Dewi Sari (Indonesian Journal of Global Health Research, 2024)
Refractive errors are the most common visual disorders throughout the world, one of which is myopia (Yeyen Ariaty et al., 2019). Myopia can be caused by genetic and environmental factors, one of which is close viewing activities such as using gadget, PC screen, or laptop for more than 10 hours without taking a break (Lestari et al., 2020). Using gadgets, PC screens, or laptops is inseparable from our daily life. More than half of the world’s population consume digital media as the main choice of communication and media channels at work. Ignoring eye health will affect eye function (Alifina, 2021). Eye diseases are still often experienced by people, so the eyes require good care (Dana, 2020).Objective: This study aims to find out the factors affecting the refractive status progression of Universitas Widya Husada Semarang Staffs. The factors analyzed include age, screen time, eyeglasses use length, and natural history of diseases.Method: This study uses a quantitative research method oriented with inductive logic, while data collection uses questionnaires with Spearman’s Rank Test on SPSS (Nursalam, 2019). With saturated sample technique, the total population and the number of samples is 35 respondents, the questionnaire used in primary data collection was carried out. Validity and reliability tests were tested on 30 respondents taken from outside the research location. Results: The study results show a significant correlation of age and screen time, but no significant correlation of eyeglasses use length and natural history of disease to the progression of refractive status. Conclusions: The research data shows that there is a significant relationship between age and length of exposure to the screen, but there is no significant relationship between the use of glasses and a history of disease on the development of refractive status.